Father’s Perspectives on Family Relationships and Mental Health Treatment Participation in the Context of Maternal Postpartum Depression - Battle, Cynthia L.; Londono Tobon, Amalia; Howard, Margaret; Miller, Ivan W. (Frontiers in Psychology, 2021)
Objective: To understand the perspectives of fathers whose partners experienced postpartum depression, particularly (1) views on how fathers and family relationships were impacted by maternal PPD, and (2) attitudes regarding inclusion of fathers within the treatment process. Method: We conducted qualitative interviews with 8 postpartum couples using a semi-structured protocol, and administered questionnaires assessing demographics, depression, and family functioning. We abstracted data from hospital records regarding the mother’s depressive episode. We summarized quantitative data using descriptive statistics, and analyzed interview transcripts using qualitative analysis techniques, focusing specifically on fathers’ input on postpartum relationships and treatment involvement. Results: Over one-third of fathers had elevated symptoms of depression, and family functioning scores suggested that most couples were experiencing dysfunction in their relationships. Qualitative analysis identified three major categories of themes, and subthemes in each category. Major themes included: (1) fathers’ experiences during the postpartum period, including not understanding postpartum mental health conditions and desiring more information, experiencing a range of emotions, and difficulty of balancing work with family; (2) fathers’ views on postpartum relationships, such as communication problems, empathy for partner, and relationship issues with other family members; (3) fathers’ attitudes towards postpartum treatment, including openness to be involved, perceived benefits, and barriers and facilitators to the inclusion of partners in treatment. Conclusion: Though barriers exist, many fathers are motivated to be included in the treatment process. In addition to supporting maternal wellbeing, fathers view treatment as a means to improve issues in the couple or family system, such as communication difficulties.